A hybrid architecture for intelligent vehicle navigation by selecting activities. (6th January 2009) - Li, Jin; Chen, Wuwei; Wang, Tanbin; Li, Bichu
An intelligent vehicle must have a proper architecture in order to work autonomously in a complicated and dynamic environment. After considering the advantages and disadvantages of the typical architecture, a hybrid architecture for intelligent vehicle navigation is presented. This architecture uses a blackboard to coordinate interactions between modules, and classifies the activities of the intelligent vehicle into reflecting activity and voluntary activity. The reflecting activity is activated by data and the voluntary activity is selected by the blackboard. The navigation task is accomplished by selecting proper activities to control the vehicle according to the environmental condition and the status of the vehicle. The theoretical analyses, simulation and experiment results show that this architecture has good intelligence and reactivity.